Ethical dilemmas in malaria drug and vaccine trials: a bioethical perspective. Issue 4 (December 1992) - Barry, M; Molyneux, M
Abstract : Malaria is a disease of developing countries whose local health services do not have the time, resources or personnel to mount studies of drugs or vaccines without the collaboration and technology of western investigators. This investigative collaboration requires a unique bridging of cultural differences with respect to human investigation. The following debate, sponsored by The Institute of Medicine and The American Society of Tropical Medicine and Hygiene, raises questions concerning the conduct of trans-cultural clinical malaria research. Specific questions are raised about the difficulties of informed consent in different cultural settings and whether there is any role for community involvement. Discussants debate whether drug and vaccine trials not approved in an industrialised country are ever defensible if performed in a third-world setting. Potential conflicting priorities between investigators are discussed and ideas regarding conflict resolution are offered.